In situ topographical chemical and electrical imaging of carboxyl graphene oxide at the nanoscale - Su, Weitao; Kumar, Naresh; Krayev, Andrey; Chaigneau, Marc (Nature communications, 2018)
Visualising the distribution of structural defects and functional groups present on the surface of two-dimensional (2D) materials such as graphene oxide challenges the sensitivity and spatial resolution of the most advanced analytical techniques. Here we demonstrate mapping of functional groups on a carboxyl-modified graphene oxide (GO–COOH) surface with a spatial resolution of ≈10 nm using tip-enhanced Raman spectroscopy (TERS). Furthermore, we extend the capability of TERS by measuring local electronic properties in situ, in addition to the surface topography and chemical composition. Our results reveal that the Fermi level at the GO–COOH surface decreases as the I D / I G ratio increases, correlating the local defect density with the Fermi level at nanometre length-scales. The in situ multi-parameter microscopy demonstrated in this work significantly improves the accuracy of nanoscale surface characterisation, eliminates measurement artefacts, and opens up the possibilities for characterising optoelectronic devices based on 2D materials under operational conditions. Mapping the distribution of functional groups on 2D materials with high resolution remains challenging. Here, the authors combine tip-enhanced Raman spectroscopy and Kelvin probe force microscopy to simultaneously examine the topography, chemical composition and electronic nature of graphene oxide surfaces with nanoscale spatial resolution.